From Unidisciplinary to Multidisciplinary Rebound Research: Lessons Learned for Comprehensive Climate and Energy Policies - Santarius, Tilman; Walnum, Hans Jakob; Aall, Carlo (Frontiers in Energy Research, 2018)
This article presents how the rebound phenomenon has evolved from only being considered from a neoclassical economic perspective to include several other disciplines such as psychology, sociology, and industrial ecology. The intention is to show how different theoretical perspectives contribute to the scientific discourse about rebound effects. We summarize key findings from the various disciplinary strains of research and highlight new research questions and needs that arise. We discuss strengths and limitations of the expansion toward multidisciplinary rebound research and suggest that a further expansion toward transdisciplinary research could be valuable. We identify the “micro-macro discrepancy” and the “cause-effect relativity” as two general challenges that have to be taken into account when rebound research becomes increasingly multi- and transdisciplinary. In the final section of the article, we present lessons learned from multidisciplinary rebound research for policies and measures that aim to mitigate rebound effects. The main finding of this article is that if policymakers aim to make climate and energy policies as “rebound-proof” as possible, findings from both energy economics and multidisciplinary rebound research have to be taken into account.